1996
DOI: 10.1200/jco.1996.14.10.2826
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic effects of chemotherapy on children with cancer: a longitudinal study.

Abstract: The present results are largely consistent with previous findings for nonirradiated groups. Treatment effects from ITC are slightly more apparent 5 to 11 years after diagnosis than at 3-year follow-up evaluation but this does not constitute a clinically meaningful difference. More noticeable are academic declines among all groups, regardless of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 44 publications
3
89
1
2
Order By: Relevance
“…Although age at diagnosis as a predictor of pursuit accuracy and of pursuit stability does not reach significance in our study, our finding of a trend level effect suggests that a young age at diagnosis as a risk factor for worse visuomotor performance in survivors of ALL may be worthy of further study. This association would be in accordance with previous studies that report a younger age at diagnosis as a risk factor for worse cognitive performance in survivors of ALL (Copeland et al, 1996;Von der Weid et al, 2003), suggesting a greater vulnerability of less mature brain structures to neurotoxic insult (Ciesielski et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although age at diagnosis as a predictor of pursuit accuracy and of pursuit stability does not reach significance in our study, our finding of a trend level effect suggests that a young age at diagnosis as a risk factor for worse visuomotor performance in survivors of ALL may be worthy of further study. This association would be in accordance with previous studies that report a younger age at diagnosis as a risk factor for worse cognitive performance in survivors of ALL (Copeland et al, 1996;Von der Weid et al, 2003), suggesting a greater vulnerability of less mature brain structures to neurotoxic insult (Ciesielski et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…CNSdirected chemotherapy for ALL, consisting of intrathecal methotrexate, alone or in combination with cytarabine and corticosteroids, and of systemic methotrexate and corticosteroids, is associated with central neurotoxicity (Kerr et al, 2001;Surtees et al, 1998). Various studies have demonstrated visuomotor deficits in relationship with other cognitive impairments in children with ALL after treatment with chemotherapy only (Copeland et al, 1996;Kingma et al, 2001;Lesnik et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of sufficient data from pediatric GSCT patients, the suspected impact of treatment on cognitive functioning has been extrapolated from other diseases and treatments, ie cranial irradiation and chemotherapy for acute lymphocytic leukemia (ALL) or CNS tumors, [1][2][3][4][5][6] the effects of which were demonstrated to be dose-and agerelated. It has been hypothesized that pre-HSCT conditioning regimens, including total body irradiation (TBI) have a detrimental effect on children undergoing HSCT.…”
mentioning
confidence: 99%
“…Copeland et al (20) concluded that children with cerebellar tumors and non-irradiation therapy in early infancy have only minimal declines in neurocognitive development compared with patients treated with cranial radiotherapy. Further, this group emphasized the possible late effects of intrathecal chemotherapy (21). Mulhern et al observed a decline of the IQ scores in patients treated for ALL with cranial radiation and intrathecal methotrexate or with chemotherapy (22).…”
Section: Discussionmentioning
confidence: 99%